Governing migration beyond the state Europe, North America, South America, and Southeast Asia in a global context - Geddes, Andrew 1965- (Oxford University Press, 2021)
International migration has become a salient concern in global politics but there is also significant variation in governance responses. By focusing on four key world regions - Europe, North America, South America, and Southeast Asia - this book explores the underlying factors that shape governance responses. Rather than focusing on the more visible outputs or outcomes of governance processes such as laws and policies, this book opens the 'black box' of migration governance to reveal how understandings and representations of the causes and effects of migration held by key governance actors in these four regions have powerful effects, not only on governance outcomes, but more broadly on the prospects for global migration governance. By doing so, the book shows how migration governance systems through their operation and effects can shape migration - in its various forms - and the lived experiences of migrants. --
Keywords: Internationale Migration; Einwanderungspolitik; Auswanderungspolitik; Migrationspolitik; Emigration and immigration / Government policy; Europe / Emigration and immigration; North America / Emigration and immigration; South America / Emigration and immigration; Southeast Asia / Emigration and immigration; Emigration and immigration; Europe; North America; South America; Southeast Asia